Penerapan Metode Seventools untuk Meningkatkan Kualitas Produksi di CV. Budidaya Jamur Sejati - Widad, Aisyatul (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This internship was conducted at CV. Budidaya Jamur Sejati, a company engaged in oyster mushroom cultivation. The objective of this study is to analyze and improve production quality by implementing the Seven Tools method as a quality control tool. The method includes: check sheet, Pareto chart, fishbone diagram, histogram, control chart, scatter diagram, and flowchart. Data was collected over a 12-week period through direct observation, interviews, and analysis of weekly inspection sheets. The results show that out of 88,932 total production units, there were 1,375 defective units (approximately 1.5%), with the most frequent defects being: unspread mycelium (35%), underfilled baglog (34%), and leaky plastic bags (31%). The fishbone diagram identified root causes from human factors, unstandardized work methods, substandard raw materials, and uncontrolled environmental conditions. The control chart indicates that the production process remains within control limits, although there is a trend approaching the upper limit.